2021
DOI: 10.1101/2021.02.22.432226
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systems approaches identify the consequences of monosomy in somatic human cells

Abstract: Chromosome loss that results in monosomy is detrimental to viability, yet, it is frequently observed in cancers. How cancers survive with monosomy is unknown. Using p53 deficient monosomic cell lines, we found that chromosome loss impairs proliferation and genomic stability. Transcriptome and proteome analysis revealed a partial compensation of the gene dosage changes that mitigates the effects of chromosome loss. Monosomy triggers global gene expression changes that differ from the effects of trisomy. We show… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 64 publications
1
10
1
Order By: Relevance
“…Interestingly, the existence of protein-level compensation and its higher degree for protein complex genes were true not only for DNA gains, but also for DNA losses. Consistent with our findings, a recent study reported protein-level compensation after chromosome loss (Chunduri et al, 2021) although in this study no significant difference was reported between complex and non-complex genes, perhaps due to the limited number of genes on the lost chromosomes. The protein compensation for complex genes of DNA gains is thought to occur through protein degradation of the overabundant subunits (McShane et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, the existence of protein-level compensation and its higher degree for protein complex genes were true not only for DNA gains, but also for DNA losses. Consistent with our findings, a recent study reported protein-level compensation after chromosome loss (Chunduri et al, 2021) although in this study no significant difference was reported between complex and non-complex genes, perhaps due to the limited number of genes on the lost chromosomes. The protein compensation for complex genes of DNA gains is thought to occur through protein degradation of the overabundant subunits (McShane et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Studies performed on single cancer cell lines harboring a few chromosome gains have suggested that human cells similarly overexpress most proteins on gained chromosomes 24,[42][43][44] , with ribosomes and some protein complex subunits exhibiting dosage compensation 24,41,42,45 . Additionally, while chromosome loss events outnumber chromosome gain events in most tumors 46,47 , the cellular effects of chromosome losses in human cancers have not been comprehensively explored 48 .…”
Section: Introductionmentioning
confidence: 99%
“…Although in monosomies this downregulation was previously attributed to haploinsufficiency of ribosomal genes (Chunduri et al, 2021), our data suggest that chromosome gains can possibly also lead to deregulation of these pathways, possibly due to a general aneuploidy-induced stress response (Terhorst et al, 2020). Taken together, although trisomic cells and monosomic cells display different transcriptional responses, the majority of these differences can be explained by their CIN phenotype.…”
Section: Trisomic Clones Show Cin-mediated Differential Expressionmentioning
confidence: 46%
“…The different effects of monosomies and trisomies on CIN have not been studied extensively as most model systems studying the effects of aneuploidy on CIN only focused on chromosome gains (Nicholson et al, 2015;Passerini et al, 2016;Zhu et al, 2012). However, recently it was documented that certain monosomies can trigger a CIN phenotype (Chunduri et al, 2021). There might be several explanations for this apparent discrepancy.…”
Section: Monosomies Are Chromosomally Stablementioning
confidence: 99%
See 1 more Smart Citation